Performance analysis on voip for kolej kediaman 2 & 3, Universiti Malaysia Pahang - Ko, Desmond Khang Siang (2014)
Voice over Internet Protocol (VoIP) is a useful Technology that allows users able to make unlimited free call no matter is local or international call. With this technology, the voice can be transported through over data networks. Unfortunately, the voice data will cope with some traffic that can affect the quality of VoIP calls. In this research, the maximum number of concurrent VoIP users will be estimated based on three factors which are packet jitter, packet end to end delays and MOS value. Besides, with the likes of Internet application such as video streaming, downloading of video and audio, online gaming which can directly affected the performance of VoIP. Therefore, two types of simulation scenarios can be done. First scenario is a campus network with VoIP application only. While the second scenario is a campus network with applying VoIP application and some external traffics such as HTTP and video streaming. The result these two scenarios will simulate by using OPNET modeler 14.5. In the testing phase, the number of clients in each scenario increased gradually until the threshold value for packet jitter, packet end to end delays and MOS are unacceptable. After that, the result that obtained from the simulation experiment will be analyzed and recommend the number of VoIP users for each factor. At the end, all the recommended number of users in each factor will combine in a table form and analyze again in order to determine the most recommended maximum number of VoIP users for each scenario. As a conclusion of this research, the recommended number of \ToI[P users for scenario 1 is less than 900 users while for scenario 2 is less 700 users.